Cu(Ⅰ)@MIL-100(Fe)π complex adsorbent and its preparation method and application
By introducing one-price copper ion site during the process of Mil-100 (Fe) synthesis, CU (Ⅰ)@MIL-100 (Fe) π complexing agent is prepared, which solves the low adsorption capacity of the existing CO adsorbent and choice. The problem of low sexuality has achieved efficient CO adsorption and selective separation.
Patent Information
- Application Number
- CN202211260825.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-10-14
- Publication Date
- 2025-01-28
- Estimated Expiration
- 2042-10-14
AI Technical Summary
The existing CO adsorbents have problems such as low adsorption capacity, low adsorption rate, low adsorption selectivity and complex preparation process.
Through one-step method, a one-price copper ion site is introduced when synthetic MIL-100 (Fe), preparing CU (I)@MIL-100 (FE) π complexing agent. Synthesis under the atmosphere or vacuum conditions.
Significantly improves the adsorption and selectivity of CO. Under 25 ° C and 1000MBAR conditions, the CO adsorption volume can reach 4.16mmol/g, which is increased by 502%compared to the MIL-100 (Fe) adsorbent performance, and maintains good adsorption performance And regeneration performance.
Smart Images

Figure CN115888672B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of material chemistry, and specifically relates to a Cu(Ⅰ)@MIL-100(Fe)π complex adsorbent and a preparation method and application thereof. Background Art
[0002] At present, the contradiction between the growing demand for energy and environmental pollution has become a global hot issue. The combustion of fossil energy will produce a large amount of pollutants and cause environmental pollution. Fuel oil is a widely used fossil energy. Hydrogen is considered to be the most important clean and renewable energy for the future of sustainable energy, but its efficient use still has great difficulties. The industry adopts the methane reforming hydrogen production process. Methanol hydrogen production is considered to be one of the most promising hydrogen production technologies for hydrogen fuel cells, but the hydrogen produced by this method often contains carbon monoxide impurity gas. A trace amount of CO will poison the catalyst in the fuel cell, thus affecting the normal operation of the battery, especially for hydrogen fuel cells with platinum as the catalyst. The CO content must be as low as 0.2ppm, so methanol reforming hydrogen production must be purified. Deep cold separation method is also called low temperature distillation method. In fact, it is due to the difference in physical and chemical properties of different gas molecules. The gas is liquefied at low temperature and high pressure, and then heated and distilled to obtain pure component gases with different boiling points. As the separation and purification proceeds, the concentration of the gas decreases, making the separation more difficult. It is necessary to increase the pressure, reduce the liquefaction temperature and increase the number of distillation plates to improve the separation effect. Obviously, low temperature and high pressure operation not only requires huge energy consumption, but also has high equipment construction and maintenance costs. Therefore, developing and exploring new gas separation alternatives is the general trend of modern society and industry.
[0003] Adsorption separation is a method that utilizes the adsorption capacity and selectivity differences of adsorbents for different gas components to achieve efficient separation through adsorption enrichment and desorption of adsorption beds. According to different desorption regeneration methods, it can be divided into temperature swing adsorption (TSA) and pressure swing adsorption (PSA). Temperature swing adsorption achieves regeneration separation based on the difference in adsorption capacity of adsorbents at different temperatures, and pressure swing adsorption achieves regeneration separation based on the difference in adsorption capacity of adsorbents at different pressures. Obviously, the heating-cooling process through temperature change is extremely energy-consuming. In contrast, the PSA process has a faster regeneration rate, low energy consumption, simple equipment and high degree of automation, and is easy for large-scale industrial production. At present, many types of adsorbents, such as porous carbon, porous organic polymers, metal organic frameworks, etc., are being widely studied and have obvious performance effects. Therefore, adsorption separation technology is expected to replace cryogenic separation technology in the near future.
[0004] Chinese patent CN108421532A discloses a method for preparing a carbon monoxide adsorbent with a metal organic framework material as a carrier. The adsorbent uses a metal organic framework material as a carrier, and then a divalent copper salt and a trivalent vanadium salt are simultaneously introduced into the carrier material to obtain a metal organic framework material loaded with copper ions and vanadium ions. The adsorption amount of carbon monoxide by the prepared adsorbent at 25°C is 13.25mL / g. Chinese patent CN104190364A discloses a low-toxic preparation method of MIL-100 (Fe) crystals with high adsorption capacity for CO. Sodium fluoride is used as a reaction aid instead of toxic hydrofluoric acid, which reduces the toxicity of the prepared MIL-100 (Fe) crystal material, and the obtained MIL-100 (Fe) crystal material has a high working adsorption capacity for CO. Chinese patent CN106315613A discloses a new type of 13X molecular sieve for CO adsorption and its preparation method and application. The adsorbent prepared by this method has high CO selectivity, CO yield and CO recycling amount. The preparation process is simple, which effectively reduces the preparation and use costs of the adsorbent. Chinese patent CN112705180A discloses a preparation method of an adsorbent for CO pressure swing adsorption, which uses an organic amine to treat the modified carrier in gas-solid phase, and then mixes and shapes it with a copper source to obtain an adsorbent precursor, which solves the problem of low mechanical strength and low CO adsorption efficiency of conventional adsorbents.
[0005] In summary, although some preparation methods of adsorbents for adsorbing carbon monoxide have been reported in previous literature, the existing adsorbents have the following problems: a. The pore volume and specific surface area of the adsorbent are low, and the adsorption amount is low; b. The selectivity for carbon monoxide is not high, and the separation effect is not obvious in the hydrogen and carbon monoxide separation system; c. The preparation conditions are harsh and the synthesis steps are complicated; d. The copper ion dispersion of the π-complex adsorbent with copper ions as the adsorption site is low. Therefore, the existing carbon monoxide adsorbents need to be improved. Summary of the invention
[0006] The present invention aims to solve the problems of low adsorption capacity, low adsorption rate, low adsorption selectivity and complex adsorbent preparation process of existing CO adsorbents. To this end, one purpose of the present invention is to propose a Cu(Ⅰ)@MIL-100(Fe)π complex adsorbent and its preparation method and application. By introducing monovalent copper ion sites during the synthesis of MIL-100(Fe) in a one-step method, the entire preparation process is safe and simple, and does not require synthesis under harsh conditions such as dry inert atmosphere or vacuum, which is environmentally friendly and has low energy consumption. In addition, the Cu(Ⅰ)@MIL-100(Fe)π complex adsorbent prepared by this method can greatly improve the adsorption capacity of carbon monoxide of the organic metal framework material MIL-100. At a temperature of 25°C and a pressure of 1000mbar, the optimal CO adsorption capacity can reach 4.16mmol / g, which is 502% higher than that of the MIL-100(Fe) adsorbent. It also has high specific surface area and pore volume. Moreover, the adsorbent can maintain good adsorption performance and good regeneration performance at room temperature, and is suitable for the adsorption and separation of carbon monoxide, and has good CO adsorption selectivity.
[0007] In one aspect of the present invention, the present invention provides a method for preparing a Cu(Ⅰ)@MIL-100(Fe)π complex adsorbent. According to an embodiment of the present invention, the method comprises: first mixing a divalent copper salt, a trivalent iron salt, an organic ligand and deionized water, then reacting the mixture, and finally washing, drying and grinding the reaction product to obtain a Cu(Ⅰ)@MIL-100(Fe)π complex adsorbent.
[0008] According to the method for preparing a Cu(Ⅰ)@MIL-100(Fe)π complex adsorbent according to an embodiment of the present invention, a divalent copper salt, a trivalent iron salt, an organic ligand and deionized water are first mixed, then the mixture is reacted, and finally the reaction product is washed, dried and ground to obtain a Cu(Ⅰ)@MIL-100(Fe)π complex adsorbent. The present invention synthesizes a Cu(Ⅰ)@MIL-100(Fe)π complex adsorbent by a one-step method, and has the following advantages over the prior art: (1) Currently, most adsorbents used to load copper ions are activated carbon materials, but the activated carbon itself has a small adsorption specific surface area, while the Cu(Ⅰ)@MIL-100(Fe)π complex adsorbent uses MIL-100(Fe) with a larger specific surface area as a matrix, and its pore size is 1.33 to 2.5 times the kinetic diameter of carbon monoxide, which has a better adsorption effect; (2) The existing π complex adsorbent preparation method is mostly an ion exchange method, which cannot uniformly load copper ions in the carrier pores, nor can it control the loading amount of copper ions. The present invention uses MIL-100(Fe) as a carrier and copper salt as a copper source. In the synthesis process of MIL-100(Fe), copper ions are encapsulated in the pores of the carrier. The divalent iron reducing sites of MIL-100(Fe) are used to reduce the divalent copper ions to monovalent copper ions, and the Cu(Ⅰ)@MIL-100(Fe)π complex adsorbent is prepared in one step. It has the advantages of low cost, simple process, and environmental friendliness, and can be used for carbon monoxide adsorption evaluation; (3) The traditional impregnation method and the double solvent method are both secondary loading. There are problems of uneven stirring and uneven mixing caused by large sample particles during the loading process, which causes copper ions to agglomerate on the sample surface, making the copper dispersion uneven. The surface and pores of the present application are loaded with more uniform monovalent copper ions, providing π complexation, which greatly improves the adsorption amount. In summary, the present application uses copper salt as the copper source and MIL-100(Fe) as the matrix to obtain the Cu(Ⅰ)@MIL-100(Fe)π complex adsorbent through a one-step synthesis, which has the advantages of high activity, high stability, high regeneration, high adsorption capacity and environmental friendliness. Moreover, the Cu(Ⅰ)@MIL-100(Fe)π complex adsorbent of the present application is easy to operate in the adsorption and separation of carbon monoxide, and has a good adsorption effect.
[0009] In addition, the method for preparing the Cu(I)@MIL-100(Fe)π complex adsorbent according to the above embodiment of the present invention may also have the following additional technical features:
[0010] In some embodiments of the present invention, the mass ratio of the divalent copper salt, the trivalent iron salt and the organic ligand is (0.1-1.0): (3.8-4.5): (1.8-2.0). The inventors found that the introduction of copper can effectively improve the CO adsorption performance, but too much copper is not conducive to crystallization.
[0011] In some embodiments of the present invention, the divalent copper salt comprises a mixture of at least one or more copper salt powders of copper nitrate, copper chloride, copper acetate, copper oxalate and copper sulfate. Further, the divalent copper salt is preferably copper nitrate. The inventors have found that copper nitrate is not easily hydrolyzed and is easy to coordinate with ligands, which is beneficial to improve the crystallinity of the Cu(Ⅰ)@MIL-100(Fe)π complex adsorbent.
[0012] In some embodiments of the present invention, the ferric iron salt comprises a mixture of at least one or more iron salt powders of ferric chloride, ferric sulfate, ferric acetate and ferric nitrate. Further, the ferric iron salt is preferably ferric nitrate. The inventors have found that ferric nitrate is not easily hydrolyzed and is easy to coordinate with ligands, which is beneficial to improve the crystallinity of Cu(Ⅰ)@MIL-100(Fe)π complex adsorbent.
[0013] In some embodiments of the present invention, the organic ligand comprises trimellitic acid.
[0014] In some embodiments of the present invention, the mixing comprises: stirring the mixture at room temperature for 15 to 25 minutes, and then ultrasonicating the mixture for 15 to 25 minutes.
[0015] In some embodiments of the present invention, the reaction comprises: heating the mixture at 90-100° C. for 10-15 h.
[0016] In some embodiments of the present invention, the washing comprises: washing the reaction product with deionized water at 70-90° C. for 2-6 hours, and then washing with ethanol at 50-70° C. for 1-5 hours.
[0017] In some embodiments of the present invention, the drying comprises: drying the reaction product at a constant temperature of 90 to 110° C. for 10 to 13 hours.
[0018] In the second aspect of the present invention, the present invention proposes a Cu(Ⅰ)@MIL-100(Fe)π complex adsorbent. According to an embodiment of the present invention, the Cu(Ⅰ)@MIL-100(Fe)π complex adsorbent is prepared by the above method. Therefore, the Cu(Ⅰ)@MIL-100(Fe)π complex adsorbent has the advantages of high activity, high stability, high regeneration, high adsorption capacity and environmental friendliness, and is easy to operate in carbon monoxide adsorption separation, and has a good adsorption effect.
[0019] In the third aspect of the present invention, the present invention proposes an application of a Cu(Ⅰ)@MIL-100(Fe)π complex adsorbent. According to an embodiment of the present invention, the Cu(Ⅰ)@MIL-100(Fe)π complex adsorbent is prepared by the above method, and the application includes application in the field of selective adsorption and separation of carbon monoxide and hydrogen. As a result, the Cu(Ⅰ)@MIL-100(Fe)π complex adsorbent can greatly improve the adsorption amount of carbon monoxide of the organic metal framework material MIL-100. Under the conditions of a temperature of 25°C and a pressure of 1000mbar, the CO adsorption amount can reach a maximum of 4.16mmol / g, which is 502% higher than the performance of the MIL-100(Fe) adsorbent.
[0020] Additional aspects and advantages of the present invention will be given in part in the following description and in part will be obvious from the following description, or will be learned through practice of the present invention. BRIEF DESCRIPTION OF THE DRAWINGS
[0021] The above and / or additional aspects and advantages of the present invention will become apparent and easily understood from the description of the embodiments in conjunction with the following drawings, in which:
[0022] Figure 1 It is a carbon monoxide isothermal adsorption test diagram of the adsorbents of Examples 1 to 9 and Comparative Examples 1 to 3;
[0023] Figure 2 It is a hydrogen isothermal adsorption test diagram of the adsorbents of Examples 1 to 9 and Comparative Examples 1 to 3;
[0024] Figure 3 The carbon monoxide / hydrogen selectivity diagrams of the adsorbents of Examples 1 to 9 and Comparative Examples 1 to 3 are shown. DETAILED DESCRIPTION
[0025] In order to make the above-mentioned objects, features and advantages of the present invention more obvious and easy to understand, the specific embodiments of the present invention are described in detail. In the following description, many specific details are set forth to facilitate a full understanding of the present invention. However, the present invention can be implemented in many other ways different from those described herein, and those skilled in the art can make similar improvements without violating the connotation of the present invention, so the present invention is not limited by the specific embodiments disclosed below.
[0026] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those commonly understood by those skilled in the art of the present invention. The terms used in the specification of the present invention herein are only for the purpose of describing specific embodiments and are not intended to limit the present invention.
[0027] Example 1
[0028] 1.89g of trimesic acid, 0.131g of copper nitrate, 4.04g of ferric nitrate and 6mL of deionized water were mixed evenly, stirred at room temperature for 20min, then the mixture was ultrasonicated at room temperature for 20min, and finally stirred at room temperature for 20min. The mixture was heated in an oil bath at 95℃ for 12h. Each gram of the sample was stirred and washed with 200mL of deionized water at 80℃ for 5h. Each gram of the sample was stirred and washed with 200mL of ethanol at 60℃ for 3h. The sample was then dried at 100℃ under vacuum for 12h. After grinding and treatment, the tablet was formed to obtain the Cu(Ⅰ)@MIL-100(Fe)π complex adsorbent.
[0029] Embodiments 2 to 5
[0030] The Cu(Ⅰ)@MIL-100(Fe)π complex adsorbent was prepared and adsorption tested according to the steps and conditions of Example 1, except that the amount of copper nitrate added was changed. The changed conditions are listed in Table 1.
[0031] Embodiments 6 to 9
[0032] The Cu(I)@MIL-100(Fe)π complex adsorbent was prepared and adsorption tested according to the steps and conditions of Example 1, except that copper nitrate was replaced by copper sulfate and the amount of copper sulfate added was changed. The changed conditions are listed in Table 1.
[0033] Comparative Example 1
[0034] The CO adsorbent was synthesized by the impregnation method, where 1 g of MIL-100(Fe) was mixed evenly with 30 mL of water, stirred at room temperature for 10 min, and then 0.24 g of copper chloride was slowly added thereto, stirred at room temperature for 3 h, the resulting mixture was filtered, and reduced in vacuum at 200 °C for 12 h. After treatment, the mixture was pressed into tablets to obtain the Cu(Ⅰ)@MIL-100(Fe)π complex adsorbent.
[0035] Comparative Example 2
[0036] The adsorbent was synthesized by the dual solvent method. 5.93 g of MIL-100 (Fe) was mixed evenly with 200 ml of n-hexane, first ultrasonicated at room temperature for 30 min, then stirred at room temperature for 10 min, 18 ml of an aqueous solution containing 0.24 g of copper chloride was slowly added to the stirred solution, stirred at room temperature for 4 h, and reduced in vacuum at 200 ° C for 12 h. After treatment, the mixture was pressed into tablets to obtain the Cu (Ⅰ) @ MIL-100 (Fe) π complex adsorbent.
[0037] Comparative Example 3
[0038] 1.89 g of trimesic acid, 4.04 g of ferric nitrate and 6 mL of deionized water were mixed evenly and stirred at room temperature for 20 min. The obtained mixture was ultrasonicated at room temperature for 20 min. The obtained mixture was stirred at room temperature for 20 min. The obtained mixture was heated in an oil bath at 95 ° C for 12 h. Each gram of the obtained sample was stirred and washed with 200 mL of deionized water at 80 ° C for 5 h. After that, each gram of the obtained sample was stirred and washed with 200 mL of ethanol at 60 ° C for 3 h. The obtained sample was then heated at 150 ° C with an inert gas at a constant temperature for 12 h. After grinding and processing, the tablet was formed to obtain a CO adsorbent.
[0039] Adsorption experiment test: On the intelligent weight analyzer IGA, carbon monoxide and hydrogen adsorption tests were performed using the samples obtained in Examples 1 to 9 and Comparative Examples 1 to 3. The purity of carbon monoxide in the gas is 99.9%, and the purity of hydrogen is 99.99%. The experimental conditions for the activity test of the adsorbent are: at a temperature of 25°C and a pressure range of 0 to 1000 mbar, an adsorption test was performed on the IGA intelligent weight analyzer filled with the samples obtained in Examples 1 to 9 and Comparative Examples 1 to 3 to detect the mass change in the sample tube. Among them, Table 1 shows the addition amount and test results of components 1 to 3 of Examples 1 to 9 and Comparative Examples, Figure 1 The carbon monoxide isothermal adsorption test diagram of the adsorbents of Examples 1 to 9 and Comparative Examples 1 to 3 is shown in FIG. Figure 2 It is a hydrogen isotherm adsorption test diagram of the adsorbents of Examples 1 to 9 and Comparative Examples 1 to 3, Figure 3 The carbon monoxide / hydrogen selectivity diagrams of the adsorbents of Examples 1 to 9 and Comparative Examples 1 to 3 are shown.
[0040] Table 1 Component addition amounts and test results of each embodiment and comparative example
[0041]
[0042] It can be seen from the control results of the embodiments and comparative examples that since both the impregnation method and the double solvent method are secondary loading, there are problems of uneven stirring and uneven mixing caused by large sample particles during the loading process, resulting in the agglomeration of copper ions on the sample surface, thereby making the copper ions dispersed unevenly, and the surface and pores of the present application are loaded with more uniform monovalent copper ions, providing stronger π complexation, greatly improving the CO adsorption amount and CO adsorption selectivity. In addition, by introducing monovalent copper ion sites during the synthesis of MIL-100 (Fe) by a one-step method, the entire preparation process is safe and simple, and does not need to be synthesized under harsh conditions such as dry inert atmosphere or vacuum, which is environmentally friendly and has low energy consumption. Further, since ferric chloride, copper chloride, and copper sulfate are easily hydrolyzed in water and are not easy to coordinate with ligands, resulting in poor sample crystallinity, as a preferred solution, the iron source and copper source are selected as ferric nitrate and copper nitrate, respectively, which can improve the sample crystallinity, thereby improving the adsorption and CO adsorption selectivity of Cu (I) @ MIL-100 (Fe) π complex adsorbent for CO.
[0043] In the description of this specification, the description with reference to the terms "one embodiment", "some embodiments", "example", "specific example", or "some examples" etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representations of the above terms do not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described may be combined in any one or more embodiments or examples in a suitable manner. In addition, those skilled in the art may combine and combine the different embodiments or examples described in this specification and the features of the different embodiments or examples, without contradiction.
[0044] Although the embodiments of the present invention have been shown and described above, it is to be understood that the above embodiments are exemplary and are not to be construed as limitations of the present invention. A person skilled in the art may change, modify, replace and vary the above embodiments within the scope of the present invention.
Claims
1. A method for preparing a Cu(Ⅰ)@MIL-100(Fe)π complex adsorbent, characterized in that: The method comprises: firstly mixing a divalent copper salt, a trivalent iron salt, an organic ligand and deionized water, then reacting the mixture, and finally washing, drying and grinding the reaction product to obtain a Cu(Ⅰ)@MIL−100(Fe)π complex adsorbent; The mass ratio of the divalent copper salt, the trivalent iron salt and the organic ligand is (0.1-1.0): (3.8-4.5): (1.8-2.0); The organic ligand includes benzene trimellitic acid; The reaction comprises: heating the mixture at 90-100 o C for 10-15 h.
2. The method according to claim 1, characterized in that The divalent copper salt comprises a mixture of at least one or more copper salt powders of copper nitrate, copper chloride, copper acetate, copper oxalate and copper sulfate.
3. The method according to claim 1, characterized in that The ferric iron salt comprises a powder mixture of at least one or more iron salts of ferric chloride, ferric sulfate, ferric acetate and ferric nitrate.
4. The method according to claim 1, characterized in that: The mixing comprises: stirring the mixture at room temperature for 15 to 25 minutes, and then ultrasonicating the mixture for 15 to 25 minutes.
5. The method according to claim 1, characterized in that The washing comprises: firstly heating the reaction product at 70-90 o C for 2-6 h, then wash with deionized water at 50-70 o Wash with ethanol at 4 °C for 1 to 5 h.
6. The method according to claim 1, characterized in that The drying comprises: drying the reaction product at 90-100 o C constant temperature drying for 10 ~ 13 h.
7. A Cu(Ⅰ)@MIL-100(Fe)π complex adsorbent, characterized in that: The Cu(Ⅰ)@MIL-100(Fe)π complex adsorbent is prepared by the method described in any one of claims 1 to 6.
8. An application of a Cu(Ⅰ)@MIL-100(Fe)π complex adsorbent, characterized in that: The Cu(Ⅰ)@MIL−100(Fe)π complex adsorbent is prepared by the method described in any one of claims 1 to 6, and the application includes application in the field of selective adsorption and separation of carbon monoxide and hydrogen.
Citation Information
Patent Citations
Low-toxicity preparation method of MIL-100(Fe) crystal with high capacity of adsorbing CO
CN104190364A
Novel 13X-type molecular sieve for CO adsorption as well as preparation method and application thereof
CN106315613A
Carbon monoxide adsorbent prepared from MOF (metal organic framework) material as carrier as well as preparation method and application of carbon monoxide adsorbent
CN108421532A
Preparation method of adsorbent for CO pressure swing adsorption
CN112705180A
Metal-organic framework material containing dual metals and preparation method thereof
CN109384665A